1965
DOI: 10.1063/1.1761177
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the Chapman-Jouguet Theory for Liquid and Solid Explosives

Abstract: The usual treatment of unsupportad detonation, often called the Chapman-Jouguet theory, is based on four assumptions: (1) the detonation approaches a steady state, (2) the flow is laminar and onedimensional, (3) the detonation products approach a state of chemical equilibrium some distance behind the detonation rront, and (4) the detonation velocity is the minimum permitted by the conservation conditions. In a recent paper Wood and Fickett (Phys. Fluids §, 648(1963)) proposed experiments to test the validity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Since it is not known how to adjust the data for temperature, we will use the data as given. The value of y was obtained by using the results of Davis, Craig & Ramsay (1965). At 4 "C they give an initial density of 1.159 g 0111-3, a detonation velocity of 6374 m s-l, and a Chapman-Jouguet pressure of 12.2 GPa, which yields y = 2-86,…”
Section: J B Bdxilmentioning
confidence: 99%
“…Since it is not known how to adjust the data for temperature, we will use the data as given. The value of y was obtained by using the results of Davis, Craig & Ramsay (1965). At 4 "C they give an initial density of 1.159 g 0111-3, a detonation velocity of 6374 m s-l, and a Chapman-Jouguet pressure of 12.2 GPa, which yields y = 2-86,…”
Section: J B Bdxilmentioning
confidence: 99%
“…Detonation parameters calculated by the Rx2CJ method, compared with experimental data[38][39][40][41] Detonation products predicted at the CJ state in RDX, PETN, and HMX, compared to calorimeter bomb experiment37,43 Number of atoms (% of system total) included in the above products. b Some small aggregates still exist at such high temperature and pressure conditions in the CJ state.…”
mentioning
confidence: 99%
“…Plate-push measurements off the end of HE cylinders by Davis, Craig, and Ramsay [5] showed that the reaction zone length grew with charge length, which is not predicted by either the CJ or ZND theories for ideal detonations. Bdzil and Davis [6] explained these results by using a chemical reaction model allowing reaction behind the sonic zone that creates perturbations.…”
Section: Non-ideal Explosive's Evidence Of Late-time Energy Releasementioning
confidence: 95%